2010
DOI: 10.1080/01411920903165629
|View full text |Cite
|
Sign up to set email alerts
|

The cultural inertia of the habitus: Gendered narrations of agency amongst educated female Palestinians in Israel

Abstract: Key experiences are short and intense instructional episodes that students remember to have had a decisive effect on their lives and are usually equated with a sense of self‐direction and empowerment. This study analyzes gender differences in the narrations of key educational experiences of Palestinian Israeli students—an educated segment in Israeli‐Palestinian society. The results suggest that while female Palestinians in Israeli academic programs have attained more than equal gender representation, a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…This challenges the implicit promise of the ‘Net Generation’ approach toward children's status. The case study that follows is a variation of what has been identified as the ‘cultural inertia of the Habitus’ in education in Israeli Arab society (Alayan & Yair, , p. 831).…”
Section: Authorized Intergenerational Relations and Habitusmentioning
confidence: 99%
“…This challenges the implicit promise of the ‘Net Generation’ approach toward children's status. The case study that follows is a variation of what has been identified as the ‘cultural inertia of the Habitus’ in education in Israeli Arab society (Alayan & Yair, , p. 831).…”
Section: Authorized Intergenerational Relations and Habitusmentioning
confidence: 99%
“…Bourdieu's theorizations have, heretofore, not been employed much in studies focusing on religious women's agency (see, however, Alayan and Yair 2010). This lack of Bourdieuan applications reflects the currency, within feminist theory, of the notion that Bourdieu's idea of habitus is excessively pessimistic when it comes to the possibility of dissent, resistance, and change (McNay 2004, 180-181, 185;McNay 2003, 142-143).…”
Section: Habitual Agency?mentioning
confidence: 99%